Equivalence of Textual and Pragmatic Translation Methods on President Yoon Seok Yeol’s Impeachment News - Tri Nursiah Afrillianti; Moh Supardi; M. Agus Suriadi; Hilmi Akmal (Prodi Sastra Inggris, Universitas Muhammadiyah Semarang, 2026)
This research examines the translation of political terms in news coverage of President Yoon Suk Yeol's impeachment, with a specific focus on Political equivalency applied in the translation process. By comparing parallel news texts, Yonhap News (English source text) and Antara News (Indonesian target text), this research aims to examine the textual and pragmatic levels in translating political terminology in both texts. Purposeful sampling was used for data collection, and the researcher manually identified politically significant words, phrases, and expressions through note-taking. The research uses Newmark's Free Translation Method, Hans Vermeer's Skopos theory, and Mona Baker's equivalence theory. Findings reveal differences translation process between Yonhap and Antara, particularly in handling emotional tone and ideological intensity. Antara often softens or institutionalizes politically charged expressions from the source text, while maintaining pragmatic and textual equivalence based on Mona Baker's theory. However, selective word-level adjustments led to minor meaning losses. The research highlights that political news translation extends beyond the textual and pragmatic level, incorporating ideological and political dimensions influenced by the translator's intent and media norms.